PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, PENGUNGKAPAN TANGGUNG JAWAB SOSIAL, DAN KEBIJAKAN PENDANAAN TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2 - Fitri Ardian Ningsih; Sri Mulyani; Naila Rizki Salisa (Relevan : Jurnal Riset Akuntansi, 2023)
The company value is the market value that generates prosperity for shareholders if the company’s share price rises. This study aims to analyze the effect of managerial ownership, institutional ownership, disclosure of social responsibility, and funding policies on firm value. The research object used is non-cyclical consumer sector companies listed on Indonesia Stock Exchange (IDX) for the 2017-2021 period. In this study using a purposive sampling technique sampling method. There are 86 samples of this research data. The technique used is panel data regression using the Eviews 10 analysis tool. The managerial ownership and funding policies have an effect on firm value while institutional ownership and disclosure of social responsibility have no effect on firm value.